Bethroed to the enemy Viking - Styles, Michelle (Vows and Vikings., 2021)
Left for dead by a mysterious attacker, Viking warlord Kal Randrson comes around with a deep head wound and a hazy memory, yet he instantly recognizes his rescuer<U+2014>captivating Lady Cynehild, whose life he turned upside down years before. Although she<U+2019>s his enemy, they agree to a fake betrothal to expose his attacker. But is the capable, intriguing Cynehild<U+2019>s mission to help him, or has she another intention entirely?